Human Disease Isolates of Serotype M4 and M22 Group A Streptococcus Lack Genes Required for Hyaluronic Acid Capsule Biosynthesis - Anthony R. Flores (American Society for Microbiology, 2012)
ABSTRACT Group A streptococcus (GAS) causes human pharyngitis and invasive infections and frequently colonizes individuals asymptomatically. Many lines of evidence generated over decades have shown that the hyaluronic acid capsule is a major virulence factor contributing to these infections. While conducting a whole-genome analysis of the in vivo molecular genetic changes that occur in GAS during longitudinal human pharyngeal interaction, we discovered that serotypes M4 and M22 GAS strains lack the hasABC genes necessary for hyaluronic acid capsule biosynthesis. Using targeted PCR, we found that all 491 temporally and geographically diverse disease isolates of these two serotypes studied lack the hasABC genes. Consistent with the lack of capsule synthesis genes, none of the strains produced detectable hyaluronic acid. Despite the lack of a hyaluronic acid capsule, all strains tested multiplied extensively ex vivo in human blood. Thus, counter to the prevailing concept in GAS pathogenesis research, strains of these two serotypes do not require hyaluronic acid to colonize the upper respiratory tract or cause abundant mucosal or invasive human infections. We speculate that serotype M4 and M22 GAS have alternative, compensatory mechanisms that promote virulence. IMPORTANCE A century of study of the antiphagocytic hyaluronic acid capsule made by group A streptococcus has led to the concept that it is a major virulence factor contributing to human pharyngeal and invasive infections. However, the discovery that some strains that cause abundant human infections lack hyaluronic acid biosynthetic genes and fail to produce this capsule provides a new stimulus for research designed to understand the group A streptococcus factors contributing to pharyngeal infection and invasive disease episodes.